Ovine hip hemiarthroplasty: reducing dislocation - Dunlop, D. G.; Field, J. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
We present a surgical modification which can be performed during hip hemiarthroplasty, in the ovine model, that may significantly reduce the perioperative dislocation rate. A modified tenorrhaphy technique was performed on the tendinous insertion of the accessory gluteal muscle during wound closure following hemiarthroplasty. Subsequently only one of sixteen animals (6%) dislocated. This compares favourably with other studies in which significantly higher rates of dislocation have been reported. The macroscopic appearance of the repair was assessed at the time of necropsy and found to be satisfactory.
Keywords: Hip hemiarthroplasty; tenorrhaphy; dislocation